Drug and Gene Therapy for Treating Variant Transthyretin Amyloidosis (ATTRv) Neuropathy - Dardiotis, Efthimios; Kyriakides, Theodoros (Current Neuropharmacology, 2023)
Variant Transthyretin Amyloidosis (ATTRv) neuropathy is an adult-onset, autosomal dominant, lethal, multisystemic disease due to the deposition of mutated transthyretin (TTR) in various organs, commonly involving the peripheral nerves and the heart. Circulating TTR tetramers are unstable due to the presence of mutated TTR and dissociate into monomers, which misfold and form amyloid fibrils. Although there are more than 140 mutations in the TTR gene, the p.Val50Met mutation is by far the commonest. In the typical, early-onset cases, it presents with a small sensory fibre and autonomic, length-dependent, axonal neuropathy, while in late-onset cases, it presents with a lengthdependent sensorimotor axonal neuropathy involving all fibre sizes. Treatment is now available and includes TTR stabilizers, TTR amyloid removal as well as gene silencing, while gene editing therapies are on the way. Its timely diagnosis is of paramount importance for a better prognosis.
Keywords: gene therapy